Parameter Fisik Dan Kimia Perairan Kolam Untuk Menunjang Pertumbuhan Ikan Lele Dumbo (Clarias Gariepinus) - Mendrofa, Elrica April Yanti (Jurnal Perikanan dan Kelautan, 2025)
This article presents a comprehensive literature review on the impact of physical of ponds on the growth and survival of dumbo catfish (Clarias gariepinus). By analyzing various studies and scientific articles, this research summarizes information on the optimal range as well as the negative effects of temperature, pH, turbidity, and dissolved oxygen (DO) levels on the physiology and growth performance of dumbo catfish. The sources studied consistently emphasized the importance of maintaining the stability of physical variables within the limits acceptable to this species to improve efficiency in aquaculture. The synthesis also points out knowledge gaps and areas of research needed to better understand the complex interactions between the physical variables of pond waters and the biological reactions of dumbo catfish. The conclusion of this review emphasizes that proper management of the physical variables of pond waters is a key factor for success and sustainability in dumbo catfish aquaculture.